2011
DOI: 10.1038/nmat3053
|View full text |Cite
|
Sign up to set email alerts
|

Controlled enhancement of spin-current emission by three-magnon splitting

Abstract: Spin currents--the flow of angular momentum without the simultaneous transfer of electrical charge--play an enabling role in the field of spintronics. Unlike the charge current, the spin current is not a conservative quantity within the conduction carrier system. This is due to the presence of the spin-orbit interaction that couples the spin of the carriers to angular momentum in the lattice. This spin-lattice coupling acts also as the source of damping in magnetic materials, where the precessing magnetic mome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
160
5
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(177 citation statements)
references
References 27 publications
(22 reference statements)
11
160
5
1
Order By: Relevance
“…The roton-phonon interaction does not give any observable roton linewidth. The present results show the importance of both cubic and quartic vertices in superfluid 4 He, and we expect that this will have a wide-ranging impact for Bose-condensed systems in general, covering areas such as excitons in semiconductors, magnon decay [20][21][22], non-linear effects in spintronics [23,24], and strongly interacting ultracold Bose gases [25].…”
mentioning
confidence: 60%
“…The roton-phonon interaction does not give any observable roton linewidth. The present results show the importance of both cubic and quartic vertices in superfluid 4 He, and we expect that this will have a wide-ranging impact for Bose-condensed systems in general, covering areas such as excitons in semiconductors, magnon decay [20][21][22], non-linear effects in spintronics [23,24], and strongly interacting ultracold Bose gases [25].…”
mentioning
confidence: 60%
“…In summary, the SMR in Pt layers with different thicknesses [3,4,8, and 35 nm], deposited on top of YIG, was investigated for both in-plane and out-of-plane applied magnetic fields. In-plane magnetic field scans clearly show the presence of SMR for the transverse as well as the longitudinal configuration.…”
Section: Discussionmentioning
confidence: 99%
“…The ISHE has been used to detect, for example, spin pumping into Pt from various materials such as permalloy 2 (Py) and yttrium iron garnet (YIG). [3][4][5] For the opposite effect, to use Pt as a spin current injector, a charge current is sent through the Pt, creating a transverse spin accumulation by the spin-Hall effect (SHE). [6][7][8] Recently, Weiler et al 9 and Huang et al 10 observed magnetoresistance (MR) effects in Pt on YIG and related those effects to magnetic proximity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved crystallization of the garnet later yielded full mode conversion in 3mm 21 . Importantly, once highly gyrotropic YIG is grown successfully on Si, it may also find application in spintronics, for example, in spin logic and spin current generators 1,[34][35][36][37][38][39][40][41][42][43][44] . This paper will discuss the optical consequences of having seedlayers on waveguides with garnet claddings and will introduce two new garnet materials, terbium iron garnet (TIG, Tb 3 Fe 5 O 12 ) and bismuth-doped terbium iron garnet (Bi:TIG), both of which do not require seedlayers on Si or on other non-garnet substrates.…”
mentioning
confidence: 99%